Analisis Pengaruh Instrument Landing System (ILS) untuk Peningkatan Pelayanan Keselamatan di Bandar Udara Haluleo Kendari - Sabur, Fatmawati; Bahrawi, Ahmad; Agung Rahardjo, Muh. (Politeknik Penerbangan Makassar, 2020)
Instrument landing systems (ILS) at airports are very important in guiding aircraft through safe landing. The service of air navigation aids at Bandar Haluoleo Kendari has not been optimal so far. This is due to damage at the beginning of the installation. The purpose of this research is to determine the impact of ILS being less optimal on improving flight safety services. The research method used is descriptive qualitative and quantitative methods that describe the general conditions of aviation safety caused by the lack of optimal ILS and calculate the operating costs per type of aircraft that experienced a landing cancellation based on manual maintenance. The results of the study show that there is a significant influence between the lack of optimal ILS on flight safety when visibility below minima. It also has an impact on the loss of aircraft operating costs incurred by the airline, avtur losses on aircraft that experience holding / delay and time loss for passengers who use the air transportation services. Alternative problem solving is to re-optimize the use of ILS such as completing modules and refining modules by factory expert technicians or third-party procurement of ILS goods / equipment